2018
DOI: 10.21608/joems.2018.2576.1011
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Flow of Micropolar Maxwell Fluid Over Stretching Surface

Abstract: The unsteady flow of Maxwell fluid over a stretching surface is investigated in this paper numerically. The governing partial differential equations are transformed into a nonlinear ordinary differential equations by using a similarity transformation. The numerical results are guaranteed in comparison with the previous under special assumptions. The effects of elasticity number and material parameter on velocity and micro-rotation profiles are presented and discussed in aid of tables and graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The stretching surface is selected along the đť‘Ą-direction of motion, and the 𝑦-direction is chosen normal to it. The following is a mathematical formulation for the model that governs this sort of flow [6,14]:…”
Section: Mathematical Modeling and Governing Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stretching surface is selected along the đť‘Ą-direction of motion, and the 𝑦-direction is chosen normal to it. The following is a mathematical formulation for the model that governs this sort of flow [6,14]:…”
Section: Mathematical Modeling and Governing Equationsmentioning
confidence: 99%
“…Viscous and elastic procedures are offered by viscoelastic non-Newtonian fluid. The study [4][5][6] covers a number of these tactics. Using velocity slip, cross-diffusion effects were investigated by Baag et al [4], Jayachandra Babu and Sandeep [5] presented the flow of MHD Williamson fluid through a stretched surface of varied thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Madhu et al 5 distinguished the viscoelastic behavior of the flow under the influence of thermal radiation and MHD. The micropolar non-Newtonian fluid flow was examined by Elbashbeshy et al 6 They concluded that the value of maximum angular velocity is enhance due to Lorentz force; whereas, it lessened due to increase in material parameters. Hsiao 7 formulated and evaluated the problem of Carreau-Nanofluid mixed convective stagnationpoint flow with activation energy and Ohmic electric dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Elbashbeshy et al [9] studied the unsteady flow of Maxwell fluid showing that the modified skin friction increases with the elasticity parameter, magnetic field, and material parameter. Hsiao [10] used the improved parameters control method to investigate the effects of the electrical MHD ohmic dissipation forced and free convection on the Maxwell fluid with a stagnation point.…”
Section: Introductionmentioning
confidence: 99%